Analisis Perhitungan Daya Dukung Pondasi Footplate dengan Menggunakan PHP script - Ismail, M Rizky; Setyanto, Setyanto; Zakaria, Ahmad (Universitas Lampung, 2015)
Foundation as we know is part of construction. A purpose of this construction is to continue astructure load to the ground which can endure the load without settlement effect. In order toguarantee the building is on stable condition concerning from structure load or outer force like awind pressure, earthquake, etc and settlement which is more than permission limit unallowed. Toavoid unfunctional foundation structure, foundation must placed on the solid ground which canendure sttructure load without causing excessive settlement. In this era computer technologydevelop quickly. Part of that is programming using PHP script. Programming using script canmake some application to help us in our analyzing dan calculating proccess with interestingdesign , so we can operate it easily. And this program is using PHP script method . Basicallyanalyzing and calculating footplate manually can used up our time. Because on calculating thiswe use a complex method, we need program to analyze and calculate footplate foundation. Tomake a calculation simpler and quicker. Some of manual test result which are found by us ishaving 1% difference with the program. So we consider this program is able to calculate thefootplate foundationKeywords : foundation, footplate, PHP